The Impact of Brand Image and Service Quality on Customer Loyalty, with Customer Satisfaction as A Mediator - Supriyanto, Bambang; Dahlan, Kandi Sofia Senastri (International Journal of Social Service and Research, 2024)
The study conducted at PT Kennametal Indonesia, a cutting tool industry company under the Kennametal brand, aimed to assess the impact of brand image and service quality on customer loyalty, specifically focusing on customer satisfaction as a potential mediator. Employing an empirical study approach, data were gathered via a questionnaire distributed to randomly selected customers. This resulted in 111 sets of received data, with 106 deemed suitable for analysis out of the 200 distributed questionnaires. SMART PLS 3.0 was utilized to explore the relationships between independent variables (brand image and service quality) and the dependent variable (customer loyalty) while evaluating the mediating role of customer satisfaction. The findings revealed that the service quality of PT Kennametal Indonesia did not significantly impact customer loyalty towards cutting tools, and a similar lack of significant influence was observed for brand image. It is crucial to emphasize that the term "not significantly impact" indicates the absence of a statistically significant relationship between service quality or brand image and customer loyalty. However, a positive and significant correlation emerged between brand image and service quality in relation to customer satisfaction. Consequently, customer satisfaction emerged as a substantial factor positively influencing loyalty. Furthermore, customer satisfaction was identified as a partial mediator in both the relationship between brand image and customer loyalty and the relationship between service quality and customer loyalty. To enhance result interpretation, providing effect sizes or correlation coefficients would offer a more nuanced understanding of the observed relationships.